The Influence of Organizational Culture and Organizational Support on Organizational Citizenship Behavior (OCB) in Employees of Regional Public Companies - Ale Alby Romeo; Lisa Harry Sulistiyowati (International Journal Labs, 2026)
This study aims to determine the influence of Organizational Culture (X1) and Organizational Support (X2) on Organizational Citizenship Behavior (OCB) (Y) in employees of regional public companies in 2026. This study uses a quantitative approach with a verifiable descriptive method. Data was collected through a questionnaire from 108 employees who were determined using the Slovin formula with a margin of error of 5%. Data analysis techniques include classical assumption test, multiple linear regression analysis, t-test, F-test, and deter-mination coefficient analysis with the help of IBM SPSS version 29 for Windows device. The results of the study show that Organizational Culture and Organizational Support simultaneously have a positive and significant effect on Organizational Citizenship Behavior. These findings are supported by a deter-mination coefficient (Adjusted R Square) value of 0.354, which indicates that Organizational Culture and Organizational Support are able to explain the variation in OCB by 35.4%, while the rest is influenced by other variables outside the study. Partially, Organizational Culture has a positive and significant influence on OCB, similarly Organizational Support shows a positive and significant influence on OCB, with Organizational Support having a more dominant influence. The resulting regression equation shows that an increase in Organizational Culture and Organizational Support will be followed by an increase in employee OCB behavior. These findings affirm that strengthening organizational cultural values and providing fair and sustainable organizational support are important factors in encouraging employee voluntary work behaviors that support organizational effectiveness.